Impact of Migration on Welfare of Migrant Sending Households in Selected Rural Areas of Zimbabwe - Zvendiya, Ronald (Department of Social Development, 2022)
The New Economics of Labour Migration theory, recognizes family participation in migration decisions as a strategy for moving out of poverty, thus signaling potential welfare linkages between migrants and family members left behind. The current study investigates the impact of migration on welfare of migrant sending households in rural Zimbabwe using cross-sectional data. The study employed a Counterfactual approach and utilized two stage Heckman selection model to control for selection bias. The results indicated that on average, migration impacts household welfare positively but the welfare gains are not evenly distributed among households. Overall, the welfare of households with migrants would have been 5 percentage points lower if migrant members had stayed at home. Based on the findings, the main recommendation is that policy makers need to consider the removal of de facto and de jure migration restrictions.